Evaluation of Association between duration of Hospitalization in-Patient with Deep Venous Thrombosis and the type of Treatment Considering the Effect of Comorbid Diseases - Pishgahi, Mehdi; Bozorgmehr, Rama; Karimi Toudeshki, Kimia; Forouzannia, Ali (Archives of Men's Health, 2021)
Introduction: Deep vein thrombosis (DVT) is a common disease with serious risks such as pulmonary embolism and there are different anticoagulant therapies for treatment of this condition. In this study, we investigated the association between the duration of hospitalization with different treatment methods and comorbidities. Materials and methods: In this retrospective cross-sectional study, the hospital records of 213 patients with a diagnosis of acute DVT in Shohada-e-Tajrish Hospital in 2019 and 2020 were reviewed. Patients were divided into five main groups and five subgroups based on the type of treatment. Then, the association between the duration of hospitalization and different treatment methods was studied. Results: Treatment with novel oral anticoagulants (NOACs) with an average length of 2.5 days of hospitalization significantly reduces the duration of hospitalization. Combination therapy with low molecular weight heparin (LMWH) and warfarin or LMWH alone, with an average of 8.38 and 8.20 days, is preferable to treatment with unfractionated heparin (UFH) and warfarin, with an average of 9.2 days. Warfarin treatment with an average duration of hospitalization of 8.43 days is in the third place. The use of other methods has increased the duration of hospitalization. History of comorbidities including history of hospitalization, hypertension, smoking, cancer and trauma are the five comorbidities that have the greatest effect on the length of hospitalization of patients, respectively. Conclusion: According to the present study, treatment with NOACs reduces the duration of hospitalization of patients more than the other treatment methods. The second best choice is LMWH injection therapy and continuation with warfarin or starting and continuing treatment with LMWH preferable to injecting treatment with UFH and continuing with warfarin. The type of underlying disease and comorbidities had a significant effect on the duration of hospitalization.